Evolution of the wake wave excided by the sequence of the relativistic electron bunches - Vynnyk, O.K.; Anisimov, I.O. (Вопросы атомной науки и техники, 2019)
The amplitude of plasma waves, excited by the resonant sequence of electron bunches, saturates after passage of some number of bunches. This behavior was observed and simulated, using particle-in-cell code, but was not completely explained yet. Our study of this behavior was carried out via computer simulation, using modified PDP3 code − 2D3V PIC code for axially symmetric geometry and relativistic collisionless plasma. Simulation demonstrated that amplitude saturation was caused by the plasma pressing-out from the area of the most intensive wake field. This hypothesis has been verified by the obtained electrical and magnetic field spectra, temperature and density maps and density profile for various simulation times. Амплітуда кільватерної хвилі у плазмі, збудженої резонансною послiдовнiстю електронних згустків, насичується після проходження певної кiлькостi згустків. Ця поведінка спостерігалася та була змодельована на комп’ютерi, але ще повністю не пояснена. Наше вивчення цiєї поведiнки проведене на комп’ютернiй моделі з використанням модифiкованого PDP3 коду − 2D3V програмного коду, що використовує метод частинок у комiрках в аксiально-симетричнiй геометрiї та релятивiстськiй плазмi без зiткнень. Симуляція демонструє, що насичення амплітуди викликане витисненням плазми з області найбільш інтенсивного кільватерного поля. Ця гіпотеза була перевірена за допомогою отриманих спектрiв електричних та магнiтних полiв, а також просторових мап температури та густини плазми, а також профiлiв густини плазми, зроблених для рiзних моментiв часу симуляцiї. Амплитуда кильватерной волны в плазме, возбужденной резонансной последовательностью электронных сгустков, насыщается после прохождения определенного количества сгустков. Это поведение наблюдалось и было промоделировано на компьютерной модели, но пока не до конца объяснено. Проведено изучение этого поведения на компьютерной модели с использованием модифицированного PDP3 кода − 2D3V программного кода, который использует метод крупных частиц (частиц в ячейках) в аксиально-симметричной геометрии для релятивистской бесстолкновительной плазмы. Симуляция демонстрирует, что насыщение амплитуды вызвано выдавливанием плазмы из области наиболее интенсивного кильватерного поля. Эта гипотеза проверена с помощью полученных спектров компонентов электростатического и магнитного полей, а также пространственных карт температуры и концентрации плазмы, а также профилей концентрации, произведенных в разные моменты времени симуляции.